2002
DOI: 10.1001/archinte.162.9.985
|View full text |Cite
|
Sign up to set email alerts
|

Rifampin and Rifabutin Drug Interactions

Abstract: Rifampin is a potent inducer of cytochrome P-450 oxidative enzymes. A few examples of well-documented clinically significant interactions include interactions with warfarin, oral contraceptives, cyclosporine, glucocorticoids, ketoconazole or itraconazole, theophylline, quinidine sulfate, digitoxin or digoxin, verapamil hydrochloride, human immunodeficiency virus-related protease inhibitors, zidovudine, delavirdine mesylate, nifedipine, and midazolam. Recent reports have demonstrated clinically relevant interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(148 citation statements)
references
References 51 publications
1
142
0
5
Order By: Relevance
“…Verapamil, which increased the intestinal absorption of cyclosporine and tacrolimus in this study, has previously been reported to be a substrate of P-gp when used in low doses and to strongly inhibit P-gp when used high doses [8]. Furthermore, it has been suggested that rifampicin activates P-gp in vivo and in vitro [11,12]. Although there are some other studies about the effects of P-glycoprotein modulation on the bioavailability of several drugs [16][17][18], to best of the authors' knowledge, this is the first study to investigate the effects of P-gp-inhibiting and -activating drugs on the intestinal absorption of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Verapamil, which increased the intestinal absorption of cyclosporine and tacrolimus in this study, has previously been reported to be a substrate of P-gp when used in low doses and to strongly inhibit P-gp when used high doses [8]. Furthermore, it has been suggested that rifampicin activates P-gp in vivo and in vitro [11,12]. Although there are some other studies about the effects of P-glycoprotein modulation on the bioavailability of several drugs [16][17][18], to best of the authors' knowledge, this is the first study to investigate the effects of P-gp-inhibiting and -activating drugs on the intestinal absorption of immunosuppressive drugs.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, P-gp can easily be activated by some agents, such as rifampicin [11,12]. P-glycoprotein plays an important role in the intestinal absorption of immunosupressive agents, including cyclosporine and tacrolimus [13][14][15].…”
mentioning
confidence: 99%
“…Rifabutin, a drug in the same family as rifampicin (rifamycins), is also characterized by inducing the metabolism of certain drugs, although to a lesser degree than rifampicin. (Finch et al, 2002) …”
Section: Drug Group or Drugs Affectedmentioning
confidence: 99%
“…(Blumberg et al, 2003;Finch et al, 2002;Sekar et al, 2010;Spradling et al, 2002) In general, the use of rifampicin (rifabutin is preferred due to their lesser inductive effect than rifabutin) with a single PI, including the most recent, such as amprenavir and atazanavir, is considered contraindicated (level 1: very high risk), because in most cases, rifampicin produces non-efficacy PIs concentrations. Besides, most treatment guidelines for HIV/AIDS patients extend this contraindication even to PIs combined with ritonavir used as a pharmacokinetic extension agent (enhancer).…”
Section: Interactions Of Rifamycins With Protease Inhibitors (Pis) Ormentioning
confidence: 99%
See 1 more Smart Citation